Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Write equation in standard form.
y+2=-3(x-1)


Sagot :

standard form is ax + by = c

y + 2 = -3x + 3   [distributed the -3]
3x + y + 2 = 3    [added 3x to both sides]
3x + y = 1          [subtracted 2 from both sides]

3x + y = 1 should be your answer


y+2=-3(x-1)

Multiply the right side by -3 or Distribute the -3 to x-1

y+2=-3x+3

Add like terms together

So the answer is: 3x+y=1